STRATIGRAFIA E PALEOGEOGRAFIA DEL NORICO NELLE PREALPI BERGAMASCHE OCCIDENTALI (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The stratigraphy of the thick and well—bedded Norian carbonate sequence cropping out in the Southern Calcareous Alps NW of Bergamo is reviewed. The formal name Aralalta Group is introduced to include the Zorzino Limestone, the Dolomie Zonate formations and the "Brecce sommitali della Dolomia Principale" member. Five regional (A—E) and four local (Al, El, E2, E 3) facies have been distinguished in the Aralalta Group: chaotic massive breccias (A), locally bounded by encrusting organism (Al); debris flow breccias and proximal torbidites (B); torbiditic dolomitic arenites (C); thin bedded laminites— microtorbidites (D); micritic limestones, distal torbidites (E), locally thin bedded with black clay (El), bioclastic limestones with slumpings (E2) and patch reefs (E3). The Aralalta Group is time—equivalent with the upper part of the Dolomia Principale, a classic example of inner platform. The detailed study of sedimentary structures and microfacies demonstrates that the evolution of the Dolomia Principale platform margin was in Artavaggio—Val Taleggio area structurally controlled.
Keywords: Stratigraphy; Paleogeography; Paleotectonics; Upper Triassic; Carbonate platform margin—slope; Southern Alps.